Can the Nintendo WII Balance Board be Used for a Reliable Assessment of the Initiation of Gait? - Verdini, Federica; Tigrini, Andrea; Fioretti, Sandro; Mengarelli, Alessandro (IEEE transactions on instrumentation and measurement, 2022)
The Nintendo WII Balance Board (NWBB) is appreciated not only as a gaming device but also as an alternative to laboratory-grade force plate (FP) in clinical and human motion research applications. Despite its validity during postural and quasi-static motor tasks being evaluated in several studies, no hints were provided about its usability during gait initiation for anticipatory postural adjustments (APAs) analysis. In this study, the validity of NWBB was assessed by comparing temporal and spatial parameters from center of pressure (CoP) trajectories with those obtained from a dynamometric FP. The similarity between the trajectories was confirmed by the low values of root mean square error. The percentage errors in spatial parameters resulted under 10% for the whole trajectory and under 15% for the anterior/posterior and medial/lateral components, respectively. The Bland-Altman plots showed errors equally distributed around the mean difference, without a significant proportional tendency. Consistency and agreement between measures, verified by the high values of intra-class correlation coefficients, were further confirmed by temporal parameters characterized by limited errors, lower than 14%, for each gait initiation phase. The findings of the present study confirm the usability of NWBB not only for static task but also for dynamic task and can contribute to enhance the use of such device for investigating the initiation of gait in clinical and not-specialized contexts.